ACTIVITY OF SPENT CATALYSTS IN THE HYDRODESULFURIZATION OF GAS OIL - Murti, SD Sumbogo (Agency for the Assessment and Application of Technology)
Activities of spent catalysts were examined in hydrodesulfurization (HDS) of gas oil at 340oC under 50 kg/cm2 H2. Two types of spent commercial catalyst (NiMo/Al2O3 dan CoMo/Al2O3) were used in single and two-stage of reaction configuration to show the inhibition effect of the by-product such as H2S and NH3. Hydrogen renewal between stages was attempted to show additional inhibition effects of the by-products such as H2S and NH3. Spent NiMo/Al2O3 dan CoMo/Al2O3 catalysts showed contrasting activities in HDS. HDS over spent CoMo/Al2O3 was much improved by H2 refreshment.The effect of two-stage hydrodesulfurization was markedly reduced over the spent NiMo/Al2O3. Spent catalysts apparently lost their activity due to the carbon deposition, which covered the active sites more preferentially.